Comprehensive analysis of the influence of loess structure on strength on the Loess Plateau, China - Hui Cheng; Hong Li; Shaotong Jiao; Youshan He; Junfeng Deng; Huan Wei; Yixuan Song; Rui Xu (PLoS ONE, 2025)
This study examines the influence of loess structure on strength by selecting three representative regions of the Loess Plateau in northern Shaanxi as the research area. Malan loess serves as the test subject, and in-situ direct shear tests, particle flow modeling, and theoretical analysis are employed to investigate the impact of loess structure on the damage process of soil shear deformation and its internal mechanisms. The numerical simulation examines how the alteration of clay particle content, within a range of 1%−10%, affects the strength variation of the soil, as indicated by the in-situ test. The results indicate significant geographical heterogeneity in loess strength indices, with the structural properties of loess being a primary factor contributing to this variability. The primary trend indicates an increase in clay content of loess, a decrease in grit content, a relative increase in cohesion, and a relative decrease in the internal friction angle. Furthermore, the variation in cohesion is more pronounced than the internal friction angle. This article examines the relationship between loess strength and its structural properties, enhancing the concept of strength analysis. The findings will offer a theoretical foundation for investigating regional variations and the regionalization of engineering design in the loess area of northern Shaanxi.